Leadership and the Management of Project Risk, Quality and People: Case Study of Sammya Nigeria Limited - Oluwaseun Yetunde Adetutu, Obidipe; Koleosho, Ayomide; Naomi Maiguwa, Gankino (Management Analytics and Social Insights, 2025)
This study examined leadership and management of project risk, project quality, and project people, using the case study of the 10.5km Osogbo-Ikirun Road project by Sammya Nigeria Limited in Osun State, Nigeria. Planning is the core of management, as stated in the well-known Benjamin Franklin adage, “If you fail to plan, you are planning to fail.” Planning must thus be done to have effective management. Leadership in project construction is essential since human endeavors play a vital role in all construction departments. Sammya Nigeria Ltd specializes in both civil engineering and property development and was founded in 1993. It has been providing a range of construction services. The study found that Sammya Nigeria Limited, in particular, does not always benefit from one specific leadership style. Although no one leadership style has the power to affect team performance significantly, transformational leaders show that they have faith in their followers' abilities by giving them chances to have a significant impact on their work, which may result in increased productivity, extra work, and satisfaction. The skill and experience of the site staff, the base thickness, the asphalt mix, the wearing course thickness, and the quality of the materials on site are the most critical factors that can affect the quality of a project or engineering activity in Sammya Nigeria Limited. Project managers must always remain on the job site to supervise the site workers on every aspect of the work until the end of working hours.